A switch-on MRI contrast agent for noninvasive visualization of methylmercury1. Issue 60 (4th August 2015) - Singh, Gyan; Hsu, Kuang-Mei; Chen, Yu-Jen; Wu, Shou-Cheng; Chen, Chiao-Yun; Wang, Yun-Ming
<x xml:space="preserve">Abstract</x> The first Gd(iii)-based T1 MRI contrast agent, o-MeHgGad, is demonstrated for noninvasive visualization of CH3Hg+.